KAOLINITISASI DAN MOBILITAS UNSUR TANAH JARANG PADA PROFIL PELAPUKAN BATUAN GUNUNGAPI DI PUNCAK MANDEH, SUMATRA BARAT: KAOLINITIZATION AND RARE EARTH ELEMENTS MOBILIZATION OF A VOLCANIC ROCK WEATHERING PROFILE IN PUNCAK MANDEH, WEST SUMATRA - Irzon, Ronaldo; Kurnia; Sendjaja, Purnama; E. Setiawan, Verry (Buletin Sumber Daya Geologi, 2021)
The weathering process occurs on the Earth's surface, especially in tropical climates, and causes the parent rock's mobilization of elements. Weathering is interesting because it is often associated with the enrichment of economic materials such as iron, alumina, and REEs. The weathering profile of Tertiary volcanic rocks is spread across tropical Sumatra. This study aims to describe REEs' kaolinization and mobilization process on the weathering profile of volcanic rocks in the east of Mandeh Peak, West Sumatra. XRF and ICP-MS devices are utilized to measure the abundance of major oxides, trace elements, and REEs. The increase in IOL is proven to occur in the same direction as weathering levels. A triangular diagram of SiO2-Al2O3-Fe2O3T indicates kaolinization on weathering at Mandeh Peak. Feldspar and mica were prone to weathering and instantly turn into kaolinite in the early stages of weathering to explain the main oxide variations in weathering profiles. The weathering process has increased the amount of alumina and iron significantly relative to the parent rock. There is no REEs enrichment on any of the weathering horizons other than its composition on the parent rocks. Part of Ce is oxidized into Ce4+ and left on the saprolite horizon. This condition makes Ce's mobility in the direction of weathering level is different from other REEs.